(untitled) - Trần, Đình Long (Hà Nội, 1999)
Giáo trình giới thiệu tóm lược những ván đề lớn về quy hoạch phát triển năng lượng và điện lực.
Keywords: Construction industry,Construction industry,Construction industry,Electric power-plants,Electric utilities,Electric utilities; Costs,Materials management,Standards,Design and construction,Accounting,Costs